PENGARUH AKTIVA PAJAK TANGGUHAN DAN RASIO PAJAK TERHADAP KINERJA LAPORAN KEUANGAN PERUSAHAAN PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Benny Casanova; Marsellisa Nindito (Jurnal Ilmiah Wahana Akuntansi, 2014)
Influence of Tax-deferred interest earning assets and the ratio of Tax to the Financial Reports on the performance of the manufacturing companies listed on Indonesia Stock Exchange. The purpose of this research is to provide empirical evidence about the influence of tax-deffered and tax ratio on firm’s financial report performance. Unit’s analysis of this research are several manufacturing companies which listed on Indonesia Stock Exchange. This research used purposive sampling as a technique of collecting data. The number of samples collected are 72 samples. The data were processed using SPSS program version 16. The result showed that partially tax-deffered assets has an impact on firm’s financial performance with t significance test value of 0,030 or <0,05 and tax ratio has an impact on firm’s financial performance too with t significance test value of 0,330 or <0,05. Beside, simultaneously, the impact of tax-deffered assets and tax ratio on firm’s financial performance that calculated with F significance test has a value of 0,024, or <0,05 which means tax-deffered assets and tax ratio variables are simutaneously has an impact on firm’s financial performance. In this research, it was found that tax-deffered assets could affect firm’s financial performance. This is happened because the amount of an assets could affected firm’s financial performance. One the other hand, tax ratio had an impact on firm’s financial performance because of the negative position that obtained in this research showed that increasing on tax ratio could lower down firm’s financial performance. Keywords : Tax-deffered assets, Tax Ratio, Firm’s financial performance